Concussion Knowledge and Reporting Behaviors Among Collegiate Athletes. Issue 1 (January 2022) - McAllister-Deitrick, Jamie; Beidler, Erica; Wallace, Jessica; Anderson, Morgan
Abstract : Objective: The purpose of the current study was to explore knowledge surrounding sport-related concussions (SRCs) and the impact on reporting behaviors in collegiate athletes, including sex differences. Design: Cross-sectional. Setting: Institutional. Participants: Participants were 986 collegiate athletes (607 men), aged 19.7 years (SD = 1.4) from 6 institutions, who completed a survey, including items on personal/sport demographics and SRC knowledge and reporting behaviors. Interventions: Athletes were given a short (15-minute) survey to complete during team meetings and preparticipation physicals. Main Outcome Measures: Athletes' scores on the survey, and reporting behaviors (ie, whether or not they failed to report a suspected SRC and reasons for not reporting SRCs), were examined. Results: Independent samples t tests revealed female athletes scored significantly higher than male athletes on total SRC knowledge [ t (926.6) = −10.6, P < 0.01] and symptom knowledge ( t (859) = −7.0, P < 0.01). Approximately one-quarter of athletes reported continuing to play after sustaining a suspected SRC. Chi-square analyses exposed significant differences between male and female athletes failing to report a suspected SRC (χ 2 = 7.69, P < 0.01). Conclusions: Given the current findings, educational efforts aimed at collegiate athletes may not be enough. Furthermore, it is apparent that sex differences exist in SRC knowledge and reporting behaviors among collegiate athletes.